Literasi Numerasi Matematika dalam Eksplorasi Etnomatematika Tari Topeng Endel - M. Taufik Qurohman; Ali Wardana; Taufiq Abidin (Departement of Mathematics Education, 2024)
This investigation employs both empirical and theoretical methodologies to gain a comprehensive understanding and analysis of a cultural phenomenon, utilizing field records derived from collected data. The findings of this exploration indicate that the Endel Tegal Mask Dance, a traditional dance form, encompasses diverse mathematical concepts akin to those taught at the high school level, specifically delving into Vector Matter. Consequently, this traditional dance holds the potential to serve as a contextual framework in developing educational designs tailored for high school students. Beyond that, it has the capacity to reshape the perceptions of both individuals and society, fostering an awareness that mathematics is intricately linked to daily life and culture, and can be imparted in an enjoyable manner within the realm of mathematics education. The aspiration is for students to foster a closer Establishing a link with their cultural legacy and boosting their overall literacy skills.